2021
DOI: 10.3390/jcm10081772
|View full text |Cite
|
Sign up to set email alerts
|

Can Deep Learning Using Weight Bearing Knee Anterio-Posterior Radiograph Alone Replace a Whole-Leg Radiograph in the Interpretation of Weight Bearing Line Ratio?

Abstract: Weight bearing whole-leg radiograph (WLR) is essential to assess lower limb alignment such as weight bearing line (WBL) ratio. The purpose of this study was to develop a deep learning (DL) model that predicts the WBL ratio using knee standing AP alone. Total of 3997 knee AP & WLRs were used. WBL ratio was used for labeling and analysis of prediction accuracy. The WBL ratio was divided into seven categories (0, 0.1, 0.2, 0.3, 0.4, 0.5, and 0.6). After training, performance of the DL model was evaluated. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The inter- and intra-observer reliabilities of the measurements were analyzed using ICC, with ICC < 0.40 indicating poor agreement, in the range 0.40–0.75 indicating fair to good (moderate) agreement, and in the range 0.76–1.00 indicating excellent agreement. MAE was used as a measure to determine how well the CNN fit the WBL ratio [ 13 , 14 , 15 ]. MAE is a measure that indicates the difference between the actual labeled WBL ratio by A (AL) using WLR and the WBL ratio predicted by the CNN using simple knee radiographs, , with being the estimated WBL ratio of the th data, and being the ground-truth WBL ratio of the th data [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inter- and intra-observer reliabilities of the measurements were analyzed using ICC, with ICC < 0.40 indicating poor agreement, in the range 0.40–0.75 indicating fair to good (moderate) agreement, and in the range 0.76–1.00 indicating excellent agreement. MAE was used as a measure to determine how well the CNN fit the WBL ratio [ 13 , 14 , 15 ]. MAE is a measure that indicates the difference between the actual labeled WBL ratio by A (AL) using WLR and the WBL ratio predicted by the CNN using simple knee radiographs, , with being the estimated WBL ratio of the th data, and being the ground-truth WBL ratio of the th data [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, a limitation of this study was that the prediction was only possible within intervals. Therefore, a quantitative assessment that can predict the WBL ratio and translate it to an accurate point on the tibial plateau may be more intuitive for clinical use [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…33 Recent studies have demonstrated deep learning to be faster, as accurate, and more efficient compared with experts with automated measurements in orthopaedic imaging. [28][29][30][31] One of the issues in measuring the PTS is that the process is relatively laborintensive and time-consuming for busy clinicians. This also makes it more difficult to perform research on large numbers of patients that all require manual calculation of the PTS.…”
mentioning
confidence: 99%